A Facile Method Used for Simultaneous Determination of Ponceau 4R, Allura Red and Tartrazine in Alcoholic Beverages. Issue 6 (1st January 2015) - Wang, Meiling; Zhao, Jianwei
Abstract : A facile electrochemical sensor was fabricated via highly dispersing Multi-walled carbon nanotubes (MWCNTs) in ionic liquid-graphene oxides (IL-GO) "water" at room temperature. The introduction of IL (1-butyl-3-methylimidazolium hexafluorophosphate) to GO water resulted in the high dispersibility of MWCNTs and also caused fast electron transfer rates of the three dyes of Ponceau 4R (E124), Tartrazine (E102) and Allura red (E129) at the IL-GO-MWCNT composites modified glassy carbon electrode (IL-GO-MWCNT/GCE). Well-separated oxidation peaks and enhanced peak currents of Ponceau 4R, Allura red, and Tartrazine were observed at the IL-GO-MWCNT modified GCE. For individual detection, the linear responses of Ponceau 4R, Allura red, and Tartrazine were in the concentration ranges of 1.0 × 10 −9 -1.0 × 10 −6, 8.0 × 10 −10 -5.0 × 10 −7, and 1.0 × 10 −8 -1.0 × 10 −6 mol L −1 with detection limits of 8.0 × 10 −10, 5.0 × 10 −10, and 7.0 × 10 −9 mol L −1 (S/N = 3), respectively. For simultaneous determination by synchronous change of the concentrations of Ponceau 4R, Allura red, and Tartrazine, the linear response ranges were 8.0 × 10 −9 -1.5 × 10 −7, 5.0 × 10 −9 -4.5 × 10 −7 and 2.0 × 10 −8 -1.3 × 10 −7 mol L −1 with the detection limits of 6.0 × 10 −9, 3.0 × 10 −9, and 1.0 × 10 −8 mol L −1 (S/N = 3), respectively. The fabricated sensors were further applied for the detection of Ponceau 4R, Allura, red and Tartrazine in alcoholic beverages.